Quo Vadis Hudud Di Era Kontemporer: Antara Hak Tuhan Dan Hak Manusia - Muhammad Ali Magfur (Al-Syakhsiyyah: Journal of Law and Family Studies, 2024)
This study aims to analyze the thoughts of Jumah and Usaimin regarding the discourse on the application of hudud in the contemporary era. This research is a qualitative study that uses the library research method. This research is comparative-analytic in nature which is operated by deeply analyzing two fatwas from Jumah and Usaimin about the law of applying hudud in the contemporary era and then comparing the two fatwas. Primary data sources in this study were taken from the book al-Baya>n lima> yusyghilu al-az}\han and the book al-Fata>wa ash-shar'iyyah fi> al-masa>il al-'as}riyyah min 'ula>ma>' al-balad al-h{aram while secondary data the author obtained from several sources such as previous research journals, several books, and related web pages. The research results show several important points. First, Jumah and Usaimin have different opinions about the application of hudud in the contemporary era. For Jumah, the application of hudud must be suspended while Usaimin firmly rejects any attempt to suspend hudud. Jumah and Usaimin share a belief that hudud is God's absolute right that cannot be changed by anyone. However, in terms of the application of hudud in the contemporary era, the two differ in their opinions. Jumah prioritizes the humanitarian side to suspend hudud, because according to him there are several conditions that cannot be met, while Usaimin does not budge and still obliges to apply hudud. Thus, Jumah has a semi-intellectualist style of thought while Usaimin emphasizes the textualist character that is so thick.